Consensus Meeting of European Society of Neurogastroenterology and Motility on Functional Dyspepsia (2020): Have We Dotted All the I’s? - A. A. Sheptulin; O. A. Storonova; D. E. Rumyantseva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A review of the agreement issued by the European Society of Neurogastroenterology and Motility consensus meeting on functional dyspepsia in 2020.Key points. Expert votes at the consensus meeting generally confirmed the main statements of the Rome Criteria Revision IV on the definition of functional dyspepsia, its aetiology and pathogenesis, diagnosis and treatment, as well as those of the Kyoto Consensus covering the possible association of dyspeptic complaints with H. pylori infection. An absent consensus on certain statements, especially in drug efficacy evaluation, demonstrates insufficient knowledge of many issues in disease.Conclusion. Functional dyspepsia demands further investigation.